2021
DOI: 10.1007/s11302-021-09822-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ATP release in pain: role of pannexin and connexin channels

Abstract: Pain is a physiological response to bodily damage and serves as a warning of potential threat. Pain can also transform from an acute response to noxious stimuli to a chronic condition with notable emotional and psychological components that requires treatment. Indeed, the management of chronic pain is currently an important unmet societal need. Several reports have implicated the release of the neurotransmitter adenosine triphosphate (ATP) and subsequent activation of purinergic receptors in distinct pain etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 183 publications
(200 reference statements)
1
11
0
2
Order By: Relevance
“…Subsequently, we discovered that the DEGs were also associated with synaptic plasticity and learning or memory; meanwhile, our findings revealed that the downregulated DEGs in pulpitis were primarily involved in the immune system process and response to stimulus, while the upregulated DEGs were predominantly involved in the cell part, membrane part, binding, transcription factor activity protein binding, and cell process. Our verified results of qRT-PCR also showed that the DEGs involved in the pathway of immune response and synaptic plasticity were significantly downregulated, which was consistent with previous reports. , This suggested that pulpitis may evade the host’s immunity in the brain by inhibiting the host immune system and host apoptosis of infection and may also utilize autophagy , and ATP to promote metabolic rate to control the body’s immune system. We hypothesized that these signaling pathways may occur in conjunction with synaptic plasticity changes in the brain to regulate the body’s immune system. To unravel the mechanism of pulpitis pain, further in-depth proteomic studies were warranted to substantiate our results.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, we discovered that the DEGs were also associated with synaptic plasticity and learning or memory; meanwhile, our findings revealed that the downregulated DEGs in pulpitis were primarily involved in the immune system process and response to stimulus, while the upregulated DEGs were predominantly involved in the cell part, membrane part, binding, transcription factor activity protein binding, and cell process. Our verified results of qRT-PCR also showed that the DEGs involved in the pathway of immune response and synaptic plasticity were significantly downregulated, which was consistent with previous reports. , This suggested that pulpitis may evade the host’s immunity in the brain by inhibiting the host immune system and host apoptosis of infection and may also utilize autophagy , and ATP to promote metabolic rate to control the body’s immune system. We hypothesized that these signaling pathways may occur in conjunction with synaptic plasticity changes in the brain to regulate the body’s immune system. To unravel the mechanism of pulpitis pain, further in-depth proteomic studies were warranted to substantiate our results.…”
Section: Discussionsupporting
confidence: 90%
“…ATP is a co‐transmitter released along with norepinephrine and Ach from adrenergic and cholinergic terminals in peripheral tissues (Khera et al, 2004). It is involved in pain signaling at both central and peripheral levels and inhibitory pain‐related neurotransmitters in the spinal dorsal horn neurons (Barreras‐Espinoza et al, 2017; Muñoz et al, 2021; Zapata‐Morales et al, 2018). Several reports have indicated that BoNTs inhibit the pain‐evoked release of ATP in various animal models.…”
Section: Botulinum Neurotoxinmentioning
confidence: 99%
“…In homeostatic conditions, extracellular ATP is minimal due to rapid hydrolysis by surface associated nucleases including CD39 (converts ATP to AMP) and CD73 (converts AMP to adenosine), and extracellular nucleosides (degrade adenosine) (Baron et al, 2015). During inflammation, extracellular ATP can be acutely increased by secretion via connexins or pannexins (Muñoz et al, 2021) or upon loss of membrane integrity due to cell death. In the context of Spn, the virulence factor pneumolysin colocalizes with and transcriptionally upregulates P2X 7 R on neutrophils (Domon et al, 2016).…”
Section: Non-chemokine Chemoattractantsmentioning
confidence: 99%